PEMBUATAN WEBSITE MARKET PLACE UNTUK MEMBANTU PELAKU USAHA DALAM MEMASARKAN PRODUKNYA - Rendy Gunawan; Bambang Prijambodo; Hendra Dinata (Perpustakaan Universitas Surabaya, 2018)
Development of the internet is used to increase the financial value by businesses to market and sell their products more widely and easily.Through research that has been done by using a questionnaire, note that today many people who are interested in selling products online dropship to be able to improve their income, but this time needed a system that could streamline the transaction process of dropship. Please also note that the activities of the bargain in shopping can also increase the value of customer satisfaction.Currently the number of inquiries for online transactions face to face and COD(Cash On Delivery) also known increasing, especially for certain types of products, but many sellers who do not want to serve him because of the safety factor and the authenticity of the transaction. Therefore, this thesis aims to create a website marketing, selling products with features that can allow the user to make the sale of products with the dropship system that can automatically shorten transaction dropship today. And combining the bargaining system into the e-market place to increase user satisfaction in transactions and systems that can improve the sense of security is to meet the seller in the transaction and COD which are not provided by the e-market place that has been present in Indonesia at this time.